2019
DOI: 10.17671/gazibtd.547122
|View full text |Cite
|
Sign up to set email alerts
|

Blokzinciri Teknolojisi Nedir ? Ne Değildir ?: Alanyazın İncelemesi

Abstract: Günümüzde iş yapış şekillerimiz ve alışkanlıklarımızı değiştiren bilgi ve iletişim teknolojileri hızını kesmeden rolünü devam ettirmektedir. Bu hızlı değişime ülkeler, politika belirleyiciler, araştırmacılar ve bunlardan ciddi şekilde etkilenen iş dünyasının ayak uydurması ve katkı sağlayacak teknolojilerin iş süreçlerine dahil edilmesi önemlidir. Bu noktada dijital paralarla adını konuşur olduğumuz blokzinciri (blockchain) kavramı ortaya çıkış şekli ve hızı 20.yy sonlarında ortaya çıkan internet kavramına ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Aylak (2022) concluded that in his study, the use of technology is still at the beginning stage, and that not all logistics enterprises can use this technology, since an expert will be needed due to the difficulty of comprehending this technology in the absence of a standard application. Similarly, Tanrıverdi (2019) concluded in his study that researchers and businesses do not understand the structure of blockchain technology and make mistakes to satisfy their needs.…”
Section: Literature Analysis On Blockchain Technologymentioning
confidence: 99%
“…Aylak (2022) concluded that in his study, the use of technology is still at the beginning stage, and that not all logistics enterprises can use this technology, since an expert will be needed due to the difficulty of comprehending this technology in the absence of a standard application. Similarly, Tanrıverdi (2019) concluded in his study that researchers and businesses do not understand the structure of blockchain technology and make mistakes to satisfy their needs.…”
Section: Literature Analysis On Blockchain Technologymentioning
confidence: 99%
“…Commonly, Blockchain is classified into two groups as public and private. Consortium Blockchain is also encountered as a third type [29].…”
Section: Blockchainmentioning
confidence: 99%
“…Akıllı sözleşmeler, birtakım kurallara bağlı işlemler için kullanılmaktadır, fakat diğer işlemler için kullanımı bir zorunluluk değildir. Kullandığı bu tür yapılarla birlikte, blokzincirinin sahip olduğu merkezi olmayan dağıtık yapı, şeffaflık ve kriptografik algoritmalar zamanla kriptoparalara olan yönelimi arttırmıştır [5]. Blokzinciri teknolojisiyle geliştirilmiş ilk kriptopara birimi Bitcoin(BTC)'dir.…”
Section: Gi̇ri̇ş (Introduction)unclassified